Company Divestment: Applicability of Existing IT Governance Frameworks - Annamaré Wolmarans; Neels Kruger; Neil Croft (International Journal of Computing and Informatics (IJCANDI), 2016)
The successful accomplishment of a divestiture is generally calculated by the dimension of accomplishment in realizing the elemental strategic goal that the company set out to achieve when adopting a divestment strategy. The paper will highlight the substantial role that IT has to fulfil in bringing company divestment to completion by investigating if any one of the existing IT Governance frameworks and standards could be implemented or adopted to serve as a managerial and governance framework towards company divestment. The IT department has a fundamental function to fulfill in the disentanglement of systems and IT infrastructure. In order to achieve this goal it is imperative to have a well-defined IT governance framework to guide the disentanglement processes and ensure the smooth execution of the IT divestment process.